A modular fuzzy control approach for two-wheeled wheelchair - Ahmad, Salmiah; Siddique, Nazmul H.; Tokhi, M. Osman (Springer, 2011)
Wheelchairs on two wheels are becoming essential part of life for disabled persons. But designing control strategies for such wheelchairs is a challenging task due to the fact that they are highly nonlinear and unstable systems. The subtle design of the system mimics a double inverted pendulum with three actuators, one for each wheel, and one for chair position. The system starts to work with lifting the front wheels (casters) to the upright position and further with stabilizing in the upright position. The challenge resides in the design and implementation of suitable control strategies for the two-wheeled wheelchair so as to perform comparably similar to a normal four-wheeled wheelchair. A two-level modular fuzzy logic controller is proposed in this paper. A model of the standard wheelchair is also developed as a test and verification platform using Visual Nastran software integrated with Matlab.